Towards higher thermoelectric performance of Bi2Te3 via defect engineering. (15th January 2016) - Liu, Yufei; Zhou, Menghan; He, Jian
Abstract: No thermoelectric material would have attained its best performance without defects . The electrical resistivity, Seebeck coefficient, and thermal conductivity in their totality are manifestations of charge flow, phonon flow, and their interplay mediated by defects. We herein focus on the role of 0-D defects (dopants, vacancies, interstitials, and antisites), 1-D defects (dislocations), 2-D defects (grain boundaries), and 3-D defects (nanoinclusions) in a benchmark thermoelectric material Bi2 Te3 . The results give new insights into developing higher performance thermoelectric materials via defect engineering.